Miller Fisher syndrome/acute motor axonal neuronopathy overlap an atypical manifestation of malaria: a case report - Zafar, Khwaja Saifullah; Singh, P. S.; Kumar, Manoj (International Journal of Research in Medical Sciences, 2017)
Various types of neurological manifestations are described in P. falciparum/vivax malaria of which Guillian Barre syndrome and its variant like Miller Fisher Syndrome (MFS) and Acute Motor Axonal Neuronopathy (AMAN). We are reporting such an unusual case who presented with five days history of fever and weakness of three days duration. On investigations it turned out to be acute MFS/AMAN overlap with peripheral blood showing mixed infection having heavy parasitaemia of P. falciparum and P. vivax combine. All other causes of acute polyneuropathy were ruled out by history and relevant examination. Patient improved with Artemisinin based Combination Therapy (ACT) and other supportive measures.